Investigation Of Modified Shielded Metal Arc Welding (MOSMAW) For Weld Penetration Performance - Selvam, Manimaran (2017)
This study is about an investigation of modified shielded metal arc welding (MOSMAW) with tubular welding electrode. The existing shielded metal arc welding process (SMAW) was modified into MOSMAW to investigate the weld ability and performance of tubular welding electrode. In the preliminary investigation it was found that heat content and interaction of Helium (He) produced a deeper penetration depth (PD) and penetration area (PA) as compared with Argon gas (AR) with gas volume flow rate range (0 -2.5 L/min). Secondly from the weld microstructure investigation it was found that there were four weld phases that include ferrite (α) , pearlite (P) , widmanstatten ferrite (αw) and the acicular ferrite (αa) on three types of flux covered electrode (E6010,E6013 and E7018). Meanwhile hardness range was evident on the weld regions within the SMAW process. Based on , the nondestructive testing, PT and RT method the impact of moisture effect was found with the usage of E7018 tubular electrode which had weld surface defects compared to the use of E6013 tubular electrode. As for the tensile tests, E7018 had higher ultimate tensile strength (UTS) compared to E6013 electrode. The fracture mode found was ductile fracture and the guided bend test found E6013 and E7018 with fed orifice gases to have uniform face bend without the initiation of any crack. As for the weld region element analysis it was found that it had the usual element composition of carbon steel and electrode flux material in weld metal, HAZ and base metal. Moreover, the weld arc temperature measurement in the MOSMAW process with E6013 with Helium fed gases produced higher arc temperature compared to the process without gas provision. The DOE results indicated that the weld variables welding current (I), electrode travel speed (S), electrode travel feed rate (F) and volume flow rate (Q) interacted significantly with the responses bead width W, penetration depth PD, penetration area PA and dilution %D. Further investigation on the DOE samples of weld penetration depth (PD) and penetration area (PA) indicated that the interaction were proportional to welding current (I) and volume flow rate (Q).The micro hardness test result hardness rate region was found to be within the SMAW carbon steel hardness range.